Additions to the ‘Flora of Borneo : The vascular plant genera’ — I: Chewlunia (Rubiaceae) and Zygogynum (Winteraceae) - Wong, Sin Yeng (Firenze University Press, 2024)
The newly recognized genus Chewlunia Junhao Chen, P.K.Hoo & K.M.Wong (Rubiaceae: Guettardeae), with eight species (seven from the Philippines and one from Sabah), and the genus Zygogynum Baill. (Winteraceae), recently recorded for the first time for Borneo with a single, novel, species, are incorporated as entries in the Flora of Borneo: The vascular plant genera, taking the Bornean flora to 1594 native genera and 12,592 species.